Once they were hats : in search of the mighty beaver - Backhouse, Frances (ECW Press, 2015)
"Beavers, those icons of industriousness, have been gnawing down trees, building dams, shaping the land, and creating critical habitat in North America for at least a million years. Once one of the continent's most ubiquitous mammals, they ranged from the Atlantic to the Pacific, and from the Rio Grande to the edge of the northern tundra. Wherever there was wood and water, there were beavers -- 60 million (or more) -- and wherever there were beavers, there were intricate natural communities that depended on their activities. Then the European fur traders arrived. Frances Backhouse examines humanity's 15,000-year relationship with Castor canadensis, and the beaver's even older relationship with North American landscapes and ecosystems. From the waterlogged environs of the Beaver Capital of Canada to the wilderness cabin that controversial conservationist Grey Owl shared with pet beavers; from a bustling workshop where craftsmen make beaver-felt cowboy hats using century-old tools to a tidal marsh where an almost-lost link between beavers and salmon was recently found, Backhouse goes on a journey of discovery to find out what happened after we nearly wiped this essential animal off the map, and how we can learn to live with beavers now that they're returning. Frances Backhouse is the author of Children of the Klondike. She lives in Victoria, B.C. and teaches creative nonfiction at the University of Victoria"--Provided by publisher.